Ellagic acid mitigates arsenic‐trioxide‐induced mitochondrial dysfunction and cytotoxicity in SH‐SY5Y cells. Issue 2 (4th January 2018) - Firdaus, Fakiha; Zafeer, Mohd. Faraz; Waseem, Mohammad; Anis, Ehraz; Hossain, M. Mobarak; Afzal, Mohammad
Abstract: In the current study, neuroprotective significance of ellagic acid (EA, a polyohenol) was explored by primarily studying its antioxidant and antiapoptotic potential against arsenic trioxide (As2 O3 )‐induced toxicity in SH‐SY5Y human neuroblastoma cell lines. The mitigatory effects of EA with particular reference to cell viability and cytotoxicity, the generation of reactive oxygen species, DNA damage, and mitochondrial dynamics were studied. Pretreatment of SH‐SY5Y cells with EA (10 and 20 μM) for 60 min followed by exposure to 2 μM As2 O3 protected the SH‐SY5Y cells against the harmful effects of the second. Also, EA pre‐treated groups expressed improved viability, repaired DNA, reduced free radical generation, and maintained altered mitochondrial membrane potential than those exposed to As2 O3 alone. EA supplementation also inhibited As2 O3 ‐induced cytochrome c expression that is an important hallmark for determining mitochondrial dynamics. Thus, the current investigations are more convinced for EA as a promising candidate in modulating As2 O3 ‐induced mitochondria‐mediated neuronal toxicity under in vitro system.